2002
DOI: 10.1046/j.1365-201x.2003.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Strength and power changes of the human plantar flexors and knee extensors in response to resistance training in old age

Abstract: Hence, hypertrophy cannot alone justify the increase in torque, and other factors, such as an increase in individual fibre-specific tension (in the case of KE), a decrease in antagonist muscles' coactivation, an improved co-ordination and an increased neural drive of the other heads of quadriceps may have contributed to the increments in strength. The significant increase in muscle power seems particularly noteworthy with respect to daily activities involving the displacement of the body over time, namely, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
140
2
15

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(183 citation statements)
references
References 43 publications
(39 reference statements)
23
140
2
15
Order By: Relevance
“…Resistance exercise training interventions were shown effective in augmenting skeletal muscle mass, increasing muscle strength and/or improving functional capacity in the elderly (97,98,(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119) . In addition, endurance (97,98,(104)(105)(106)(107)(108)(109)(110) exercise was shown to enhance the skeletal muscle oxidative capacity, resulting in greater endurance capacity (5,120) .…”
Section: Long-term Interventionsmentioning
confidence: 99%
“…Resistance exercise training interventions were shown effective in augmenting skeletal muscle mass, increasing muscle strength and/or improving functional capacity in the elderly (97,98,(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119) . In addition, endurance (97,98,(104)(105)(106)(107)(108)(109)(110) exercise was shown to enhance the skeletal muscle oxidative capacity, resulting in greater endurance capacity (5,120) .…”
Section: Long-term Interventionsmentioning
confidence: 99%
“…These data are consistent with the American College of Sports Medicine guidelines, which recommend 70-80% intensity to produce muscle hypertrophy and strength gains (American College of Sports Medicine Position Stand, 1998). In addition, HIT has been shown to be effective for a wide range of purposes, from improving weightlifting performance for athletes (Brechue and Abe, 2002) to counteracting sarcopenia in the elderly (Ferri et al, 2003;Frontera et al, 1988). However, the high intensity required for muscle adaptation with traditional resistance exercise may not be practical, and may even be dangerous when carried out without proper supervision, in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Methodological differences make study comparisons difficult, although the majority of investigators have suggested that collagen loss occurs in older individuals [84][85][86] . A substantial component of age-related strength loss may be the result of inactivity and can be modified by an appropriate exercise program [87][88][89][90][91][92] . Studies have shown that collagen and elastin production, along with collagen fibril diameter and collagen cross-linking, decrease as a result of age 82 .…”
Section: Clinical Applicationsmentioning
confidence: 99%